Jimmy Boyle's sentiments as revealed in the manuscripts of sketches of songs and instrumental melodies - Chan, Cheong Jan; Lee, Sze May; Boyle, James P. S. (Universiti Pendidikan Sultan Idris, 2015)
Jimmy Boyle (1922-1971) is known as one of the pioneers in jazz and a composer of patriotic songs in Malaysia. Despite the numerous blogs, webpages and video uploads that mention Boyle, systematic research on his music has only begun recently. Hand- written manuscripts containing 79 sketches of songs and instrumental music by Jimmy Boyle were recovered in 2013, and these manuscripts have since undergone analysis. In this paper, we intend to identify the different dimensions of Boyle’s perspectives as a composer in producing these sketches. Three themes were created to group the different sentiments of Boyle based on the styles of composition observed in the sketches, namely, Boyle as a popular songwriter, Boyle as a jazzman and Boyle as an enthusiast in ethnic music. Boyle displayed a broad capacity in the way he used his music. He had the ability to compose in different sentiments, either as a social advocate, a layperson, a jazz artist or a knowledge seeker. He manoeuvres between these sentiments skillfully, shifting his centres of focus from Malay cultural nationalism to private expressions in English, to ‘authentic’ modern jazz, and to the music cultures of ‘others’.